No more trouble zones [videorecording (DVD)] - Ambandos, Andrea; Michaels, Jillian (Lions Gate Films, 2009)
Get into the zone with TV's kick-butt trainer, Jillian Michaels, and tackle stubborn problem areas with her sure-fire circuit training formula that combines upper and lower-body sculpting moves to obliterate fat even faster.